Neonatal Acute Myocardial Infarction of Unknown Etiology Treated with Surgical Thrombectomy. (22nd July 2013) - Ramlogan, Sandhya R.; McKee, Delores; Lofland, Gary K.; Carlson, Karina M.
Abstract Coronary artery thrombosis and resultant myocardial infarction in neonates are exceedingly rare. Seldom does a neonate survive this myocardial insult. Often there is an underlying predisposition to coronary artery thrombosis, such as thrombophilia, central line placement, or myocarditis. Treatment attempts have consisted of thrombolysis and supportive care. We present a case of acute left main coronary artery (LMCA) thrombosis of unknown etiology in a neonate, without ventricular dilatation. Flow into the LMCA was suggested echocardiographically, but a high clinical suspicion led to urgent cardiac catheterization. Once complete occlusion of the LMCA was demonstrated angiographically, emergent surgical thrombectomy was performed, which has never previously been reported.